2022
DOI: 10.1136/sextrans-2021-055368
|View full text |Cite
|
Sign up to set email alerts
|

Universal lymphogranuloma venereum (LGV) testing of rectal chlamydia in men who have sex with men and detection of asymptomatic LGV

Abstract: BackgroundLymphogranuloma venereum (LGV) is caused by Chlamydia trachomatis serovars L1-L3. This study determined the positivity for LGV testing before and after introduction of universal LGV testing of positive rectal Chlamydia trachomatis samples in men who have sex with men (MSM).MethodsFrom March 2015 to February 2018, MSM with rectal C. trachomatis were not routinely tested for LGV at the Melbourne Sexual Health Centre unless they had HIV or symptoms of proctitis. From February 2018, universal testing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…22,30 LGV in MSM is significantly underdiagnosed, and a study from Australia showed that testing all C. trachomatis -positive anorectal specimens (regardless of the MSM symptoms) results in increased detection of LGV. 31 Additionally, in our study, the opportunistic anorectal testing for LGV allowed further detection of viral infections such as HSV2 (which was found in around 5% of anorectal exudates, and for which data were non-existent for Portuguese MSM prior to our study), and some cases of early syphilis.…”
Section: Discussionmentioning
confidence: 70%
“…22,30 LGV in MSM is significantly underdiagnosed, and a study from Australia showed that testing all C. trachomatis -positive anorectal specimens (regardless of the MSM symptoms) results in increased detection of LGV. 31 Additionally, in our study, the opportunistic anorectal testing for LGV allowed further detection of viral infections such as HSV2 (which was found in around 5% of anorectal exudates, and for which data were non-existent for Portuguese MSM prior to our study), and some cases of early syphilis.…”
Section: Discussionmentioning
confidence: 70%
“…LGV positivity rates (<5%) among MSM positive for rectal CT infection, [22][23][24] and hence, our small sample size may have contributed to the failure to detect this bacterial pathogen. A quarter of anorectal LGV infections in MSM are asymptomatic, 25 and LGV requires an extended treatment regimen.…”
Section: Rectal Stismentioning
confidence: 93%
“…The current LGV cases are essentially characterized by a proctitis, manifesting with anorectal ulceration, tenesmus, anal pain and mucous or bloody discharge (anorectal syndrome) [ 5 , 6 ]. However, several cases of LGV have recently been detected in asymptomatic subjects (up to 30–40% of cases), as well as in lower-risk groups of MSM (e.g., HIV-negative patients) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%